2015
DOI: 10.18410/jebmh/2015/1184
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Acute Lymphoblastic Leukemia - A Multiparameter Study

Abstract: BACKGROUNDAcute Lymphoblastic Leukaemia (ALL), a malignancy of lymphoid lineage cells, has excellent prognosis in children. Leukemia is the most prevalent childhood cancer and Acute Lymphoblastic Leukemia (ALL) constitutes 75% of all cases. The most frequent presenting symptoms are fever, weight loss and pallor. Early detection of clinical symptoms positively affects timely diagnosis. AIMS & OBJECTIVESThe objectives of the present study were to assess frequency of presenting symptoms, laboratory data and progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(12 reference statements)
2
2
0
Order By: Relevance
“…Our present study findings are similar to Jatav et al 8 Their study was conducted at Gajra Raja Medical College, Gwalior, and they found AML to be more common than ALL which was at 55.4% and 44.6% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Our present study findings are similar to Jatav et al 8 Their study was conducted at Gajra Raja Medical College, Gwalior, and they found AML to be more common than ALL which was at 55.4% and 44.6% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the AML-to-ALL ratio was approximately 1.5:1. The finding was consistent with the findings of Kassahun et al, Idris et al, and Jatav et al 1,9,10 This study is a hospital-based study and only those patients who visited us have been included; hence, the findings are not externally valid.…”
Section: Discussionsupporting
confidence: 90%
“…When the results of peripheral blood tests lead to leukemia, then bone marrow examination, immunophenotypes, and cytogenetics must be carried out immediately to make a diagnosis. 6 Our result found 42 patients (84%) with thrombocytopenia, as one of hematopoiesis dysfunction results. Signs and symptoms related to bleeding such as melena, petechiae, bruising, nosebleed, or purpura.…”
Section: Discussionmentioning
confidence: 46%
“…Variations in the infiltration of leukemia cells into organs are related to the time of diagnosis. 6 Hepatomegaly often occurs in patients with hemoglobin <10 g / dl. In diseases that arise more slowly, hepatomegaly is followed by splenomegaly, lymphadenopathy, and hyperleukocytosis.…”
Section: Discussionmentioning
confidence: 99%